2023
DOI: 10.1021/acsenergylett.3c01508
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Crystallization and Thermal-Induced Phase Evolution in Aromatic-Based Quasi-2D Perovskites Using a Robot-Based Platform

Jiyun Zhang,
Jianchang Wu,
Yicheng Zhao
et al.

Abstract: Introducing large organic cations to form reduced-dimensional (quasi-2D) perovskites has proven to be effective in stabilizing three-dimensional perovskites. In this study, we synthesized 28 Ruddlesden–Popper-type quasi-2D perovskites using four aromatic-based cations (phenylmethylammonium (PMA), phenethylammonium (PEA), phenylpropylammonium (PPA), and phenylbutanammonium (PBA)) and systematically investigated their optoelectronic and structural properties and thermal stability. A counterintuitive finding that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Surprisingly, within the aromatic-based cation system, films with longer-chain phenylpropyl­ammonium cations exhibited reduced stability even compared to shorter-chain ones, primarily due to lattice distortion and phase mismatch. On the other hand, films containing phenylbutan­ammonium cations displayed robust stability, attributed to distinctive crystallization kinetics and a gradual phase transformation (from larger to smaller phases) driven by steric hindrance . We found that approximately 20–25 mol % (nominal n = 4–5) cation intercalation into MAPbI 3 can maximize the film stability, while higher or lower concentrations lead to inferior stability, which is termed stability bowing by analogy to band gap bowing .…”
Section: Autonomous Maps For Emerging Photovoltaics Technologiesmentioning
confidence: 80%
See 1 more Smart Citation
“…Surprisingly, within the aromatic-based cation system, films with longer-chain phenylpropyl­ammonium cations exhibited reduced stability even compared to shorter-chain ones, primarily due to lattice distortion and phase mismatch. On the other hand, films containing phenylbutan­ammonium cations displayed robust stability, attributed to distinctive crystallization kinetics and a gradual phase transformation (from larger to smaller phases) driven by steric hindrance . We found that approximately 20–25 mol % (nominal n = 4–5) cation intercalation into MAPbI 3 can maximize the film stability, while higher or lower concentrations lead to inferior stability, which is termed stability bowing by analogy to band gap bowing .…”
Section: Autonomous Maps For Emerging Photovoltaics Technologiesmentioning
confidence: 80%
“…On the other hand, films containing phenylbutanammonium cations displayed robust stability, attributed to distinctive crystallization kinetics and a gradual phase transformation (from larger to smaller phases) driven by steric hindrance. 45 We found that approximately 20−25 mol % (nominal n = 4−5) cation intercalation into MAPbI 3 can maximize the film stability, while higher or lower concentrations lead to inferior stability, which is termed stability bowing by analogy to band gap bowing. 46 These works highlighted the complex effect of the type, concentration level, and steric hindrance of intercalating cations on the perovskite stability performance.…”
Section: Intercalating-cation Engineering For Stable Quasi-2d Perovsk...mentioning
confidence: 99%
“…Subsequently, the NC solutions were mixed with polyacrylate resin as perovskite inks. The perovskite binder films with a diameter of 8 mm were obtained through drop-casting the inks on a glass substrate by a HT-robotic platform (Figure S6), as reported in our previous work. , To assess the photostability of the drop-casted FA/TDPA films (named FA/TDPA-DC films), all films were exposed to a blue LED at 450 nm with a homogeneous power density of 22 mW/cm 2 , as shown in Figure S7. As illustrated in Figure f, the different TDPA concentrations primarily affected the degradation in the burn-in part, which is associated with intrinsic defect traps.…”
Section: Resultsmentioning
confidence: 99%
“…46–48 To evaluate film homogeneity, multiple positions (13 points) with regular patterns on each sample were characterized through a high-throughput spectrometer. 49–51 The coefficient of variation (CV) of PL peak intensity extracted from these PL spectra (Fig. S16, ESI†) was calculated, as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%